The Effect of Glutathione on The Quality of Aceh Local Catfish (Clarias gariepinus) Spermatozoa After Cryopreservation - Raudhah Mahfudhah; Kartini Eriani; Zainal Abidin Muchlisin (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
The cryopreservation process might reduce the quality of spermatozoa due to an increase in the production of reactive oxygen species (ROS) compounds during cooling, freezing, and thawing. The quality of spermatozoa can be maintained by adding glutathione as an exogenous antioxidant into cryo-diluent. This study aimed to examine the effect of the addition of different doses of glutathione in cryopreservation of Aceh Local catfish (Clarias gariepinus) spermatozoa after freezing. The method used was a completely randomized design (CRD) with four treatments and four replications. Fresh semen was diluted in Ringer, 15% DMSO, and 20% Fetal Bovine Serum (FBS) and then added with glutathione antioxidants of 0.0 mgL-1, 0.5 mgL-1, 1.0 mgL-1, and 2.0 mgL-1. The parameters observed in this study were motility, integrity of the plasma membrane, fertility, and DNA integrity. The results showed that the concentration of glutathione had no effect on motility, integrity ofthe plasma membrane, or fertility, but had an effect on DNA integrity. The highest percentage of motility and plasma membrane integrity respectively was 40.50% (P3) and 70.87% (P2). Furthermore, the assessment of DNA integrity showed that there was no DNA fragmentation both treatments and fresh spermatozoa. This research is the first study regarding glutathione supplementation in cryo-diluent of Aceh Local catfish spermatozoa. Finally, the results obtained can provide information about the exact concentration of glutathione in the extender on the quality of spermatozoa of Aceh Local catfish (C. gariepinus) after the cryopreservation process. These results can also increase the success of fertility be used by the seed hall unit and the aquaculture industry to increase the productivity and supply high quality seeds.